"Don't forget Shakespeare": A qualitative pilot study into the performance evaluations of orchestra audition panelists. (January 2023) - Kegelaers, Jolan; Bakker, Frank; Kouwenhoven, Jan; Oudejans, Raôul
Auditions form the gold standard for hiring practices in symphonic orchestras around the world. Nevertheless, research examining how auditions are evaluated by panel members remains sparse. The purpose of this brief research note is to present findings from a pilot project examining the feedback content of audition panelists during a realistic mock audition. Feedback received by 16 academy members of an internationally renowned orchestra was analyzed using inductive content analysis. A key finding of this study was that panelists tended to provide much more feedback related to improving expressivity (61.8%), compared with feedback on technique (24.5%) or other factors (e.g., tuning; 13.7%). As advancing our understanding of how orchestra auditions are evaluated may have considerable practical implications for how music educators can aid students in preparing for a successful transition to the professional circuit, we hope our pilot project might spur on future work investigating this important topic.